2014
DOI: 10.1016/j.actamat.2013.10.056
|View full text |Cite
|
Sign up to set email alerts
|

Quasicontinuum study of the shear behavior of defective tilt grain boundaries in Cu

Abstract: Atomistic simulations using the quasicontinuum method are used to study the role of vacancy defects and angström-scale voids on the mechanical behavior of five tilt bicrystals containing grain boundaries (GBs) that have been predicted to exhibit characteristic deformation processes of nanocrystalline and nanotwinned metals : GB-mediated dislocation emission, interface sliding, and shear-coupled GB migration. We demonstrate that such nanoscale defects have a profound impact on interfacial shear strength and und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Many of the early studies (e.g., [5,6]) focused on understanding the grain boundary structure and energy. However, recent studies have expanded to address grain boundary sliding [7][8][9][10], migration and bulk dislocation slip transfer [11][12][13], grain boundary fracture [14][15][16] or spall [17][18][19][20], grain boundary segregation [21][22][23], phase transformations [24], grain boundary mobility [25,26], etc. In many cases, grain boundary structures have to be recreated in order to assess properties, and it is unclear whether the minimum energy structure was used or a higher energy metastable structure; hence, openly publishing grain boundary datasets in materials repositories can aid in providing a common starting configuration for these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the early studies (e.g., [5,6]) focused on understanding the grain boundary structure and energy. However, recent studies have expanded to address grain boundary sliding [7][8][9][10], migration and bulk dislocation slip transfer [11][12][13], grain boundary fracture [14][15][16] or spall [17][18][19][20], grain boundary segregation [21][22][23], phase transformations [24], grain boundary mobility [25,26], etc. In many cases, grain boundary structures have to be recreated in order to assess properties, and it is unclear whether the minimum energy structure was used or a higher energy metastable structure; hence, openly publishing grain boundary datasets in materials repositories can aid in providing a common starting configuration for these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the onset plasticity was substantially diminished by the corresponding dislocation nucleation from the inner side of the cavities. Using the QC model, Péron-Lührs et al [ 37 ] investigated the effect of nanosized cavities at grain boundaries on the shear behavior of grain boundaries in Cu. Their results showed that the nanocavities could impede atom shuffling across the interfaces, preferentially facilitate the initiation of dislocation at cavities, and soften grain boundaries, resulting in a decrease of the yield strength.…”
Section: Introductionmentioning
confidence: 99%